Репатриация на чужбину... (репатриация советских немцев 1946–1947 гг.) - Айсфельд, A. (З архівів ВУЧК-ГПУ-НКВД-КГБ, 2007)
The author investigated the process of repatriation of «Soviet» Germans in 1946–1947.